AI based Birds Sound Classification Using Convolutional Neural Networks. Issue 1 (June 2021) - Anand, R; Shanthi, T; Dinesh, C; Karthikeyan, S; Gowtham, M; Veni, S
Abstract: To classify and recognize the sounds which are produced by the birds which are used for the identification of species of the bird. The identification of bird species in captured audio files will be a transformational method for scholars, wildlife biologists and birders. In latest years, artificial neural networks have dramatically increased the detection efficiency of bird species recognition using machine learning systems. There is a lot of study in audio recognition using machine learning. This work may help for the easy identification of birds living in a locality and studying of birds' migration.